2011
DOI: 10.1016/j.compeleceng.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale texture classification and retrieval based on magnitude and phase features of complex wavelet subbands

Abstract: This paper proposes a multiscale texture classifier which uses features extracted from both magnitude and phase responses of subbands at different resolutions of the dual-tree complex wavelet transform decomposition of a texture image. The mean and entropy in the transform domain are used to form a feature vector. The proposed method can achieve a high texture classification rate even for small number of samples used in training stage. This makes it suitable for applications where the number of texture samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Through this study, the authors clearly present their experiment as the directional selectivity is enhanced by the 2D HWT by the linear combination of Hilbert transform of different Wavelet sub-bands [ 35 ]. In [ 13 , 36 ], the researchers claim that magnitude and phase spectra are combined to define texture, discriminative HF edges in an image.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through this study, the authors clearly present their experiment as the directional selectivity is enhanced by the 2D HWT by the linear combination of Hilbert transform of different Wavelet sub-bands [ 35 ]. In [ 13 , 36 ], the researchers claim that magnitude and phase spectra are combined to define texture, discriminative HF edges in an image.…”
Section: Methodsmentioning
confidence: 99%
“…Equivalent directional selectivity is possible to accomplish by adding/subtracting the different HWT pairs [ 35 ]. In [ 36 ], the researchers combine the magnitude and phase spectra for defining texture, discriminating HF edges in an image. Hence, in the activation function proposed for the Detailed Wavelet sub-bands, the Hyper-analytic wavelet phase term (the imaginary part of the complex activation) preserves the edges that occur as negative coefficients.…”
Section: Literature Surveymentioning
confidence: 99%
“…The recall is defined for the query image I q as given below: 11) where N G is the number of top matches considered. The precision is defined as follows: where 'n' indicates the number of retrieved images, f (x) is the category of 'x', Rank(I i , I q ) returns the rank of image I i (for the query image I q ) among all images of |DB| and…”
Section: Performance Measuresmentioning
confidence: 99%
“…Texture analysis and retrieval has gained wide attention in the field of medical, industrial, document analysis, surface inspection and many more. Various algorithms have been developed for texture analysis, such as multi-scale texture classification [11], mean and variance of the wavelet coefficients [12] texture features are reported in [13][14][15]. In practice texture features can be combined with color features to improve the retrieval accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Qiao et al [11] made use of the complex wavelet frame transform, and combined the magnitude and phase of the complex coefficients into a real measure to characterize the texture. Due to the approximately shift invariance and good directional selectivity of the dual-tree complex wavelet transform (DT-CWT), Celik and Tjahjadi [12] suggested that the statistical measures of magnitude and phase of the DT-CWT coefficients are better than the DWT based method. Ji et al [13] applied the multi-fractal spectrum (MFS) analysis on wavelet coefficients to extract robust texture descriptors for texture classification.…”
Section: Introductionmentioning
confidence: 99%